The relationship between thinking styles and level of externality: A study of Turkish female preschool student teachers - (:unkn) unknown (SOC PERSONALITY RES INC, 2008)
The relationship between thinking styles and level of externality is examined in this study in which 108 female preschool student teachers at Marmara University participated. The participants responded to the Thinking Style Inventory (TSI; Sternberg & Wagner, 1992) based on Stemberg's theory of mental self-government and Rotter's Internal-External Locus of Control Scale (RIELS; Rotter, 1966). The results revealed a close correspondence between thinking styles and level of externality. The findings showed that level of externality is negatively associated with legislative, judicial, hierarchic, global, and liberal thinking styles. The implications are discussed in detail.
Keywords: thinking styles; level of externality; education; locus of control; ACADEMIC-ACHIEVEMENT; SELF-ESTEEM; LOCUS; PERSONALITY; CHILDREN; PERFORMANCE; BELIEFS; MODEL